Coastal Zone Planning and Management in Istanbul - Ayat, Berna; Uzmez, Zeynep; Cevik, Esin Ozkan; Yuksel, Yalcin (MEDITERRANEAN COASTAL FOUNDATION-MEDCOAST FOUNDATION, 2007)
Vulnerable coastal areas of Istanbul like all over the world face problems such as population growth, industrialization, commercial development and tourism, and extensive exploitation of marine resources. Many places has resulted increase in erosion and flooding, loss of wetlands, pollution. In addition, the risk of natural hazards increases due to the global climate change. As a result, conflicts of interest occur more frequently and the sustainable use of natural and environmental resources is threatened. To help resolve these conflicts ICZM has developed for Istanbul coastal areas. An inventory for Istanbul Coastal zone was studied. Strategical plan aims and propositions for future planning were developed.
Keywords: BLACK-SEA; CIRCULATION; Environmental Sciences & Ecology; Geology